Edukasi Pendidikan Kesehatan tentang Efek Samping Penggunaan KB Suntik 3 Bulan dalam Jangka Panjang di RW 09 Desa Babakan - Nurul Azmi Fauziah; Afipah Destiara; Diani Hadi Lestari; Eva Puji Lestari; Restika Amalia (STIKes Ibnu Sina Ajibarang, 2025)
More than 100 million women, around 75% of women use hormonal contraception and 25% apply non-hormonal contraception according to the World Health Organization (WHO). The purpose of this counseling is to educate to increase public knowledge about the side effects of using 3-month injection contraception for a long time, especially in RW 09 Babakan Village, Ciseeng District. The method used is a lecture method with booklet media. The target of this counseling is 40 women who use contraception. The results of the questionnaire, namely from the pretest, 26 people (65%) had insufficient knowledge and the posttest, 32 people (80%) understood well. The results of the T test = - 13.733 and p value = 0.000 (<0.05) in the pretest and posttest. The conclusion shows that there is an influence of education on the side effects of using 3-month injection contraception for a long time.